2001
DOI: 10.2307/2673768
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge of and Attitudes toward the Pill: Results of a National Survey in Japan

Abstract: Legalization of oral contraceptives in Japan has led to an urgent need to educate both men and women on the inability of the pill to protect against STDs, including HIV Policymakers and providers need to recognize the importance of encouraging dual method use in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Women's social standing within the community Women's behaviour in some countries, particularly Eastern Europe and Asian countries was found by Spinelli et al Kihara et al (2001) Knowledge and attitudes towards the pill in Japan Quantitative Moursund and Kravdal (2003) Whether differences in women's autonomy can explain the relationship between education & contraceptive use (married Indian women with 1 child)…”
Section: Access To Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Women's social standing within the community Women's behaviour in some countries, particularly Eastern Europe and Asian countries was found by Spinelli et al Kihara et al (2001) Knowledge and attitudes towards the pill in Japan Quantitative Moursund and Kravdal (2003) Whether differences in women's autonomy can explain the relationship between education & contraceptive use (married Indian women with 1 child)…”
Section: Access To Servicesmentioning
confidence: 99%
“…Canadian surveys have shown lower educational levels were associated with both higher rates of missed pills and also lower familiarity with different methods available. (Fisher et al 1999b, Kihara et al 2001. Contraceptive behaviour and attitudes of Asian women were found by Moursund and Kravdal (2003) to be strongly linked to education and consequently to autonomy, and high educational levels were associated with strongest intentions to stop child-bearing.…”
Section: Contraceptive Choices and Access To Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1973 Japanese fertility resumed its decline, falling to 1.3 in 2006. Through much of this period Japanese women relied on condoms as their major means of contraception since the pill was not approved for contraceptive use until 1999 (Kihara et al 2001). By the early 1980s, when the declining TFR reached 1.7, some Japanese began to assert that restrictions on abortion were needed.…”
Section: Japanese Antinatalismmentioning
confidence: 99%
“…In a survey conducted by a group funded by the Ministry of Health and Welfare in 2000, the investigators found that the incidence rate of Chlamydia infection was 4.8% among adolescent men and women aged 15-19 years and 6.2% among those aged 20-24 years (23). Previous research has also shown that approximately one quarter of Japanese people erroneously thought that oral contraceptives prevented HIV and STD infections (24).…”
Section: The Impact Of Oral Contraceptives In Japanmentioning
confidence: 99%